Reliability test for frequency estimation of sinusoid based on LMP detection - UGuo-bing H; ULi-zhong X; AOAn-ping B; UShan-shan W; AOYan G (Tongxin xuebao)
A reliability test method based on locally most powerful (LMP) detection was proposed to evaluate the fre-quency estimation of sinusoid.The hypothesis test was created at first,and then a reference signal was generated depend-ing on the specific frequency estimation of the sinusoid.By analysis of the parameters differences from the probability distribution characteristics of the modulus of the cumulative sum series under the different two hypotheses,the reliability test for frequency estimate of sinusoid signal was performed by the proposed LMP-based statistic and threshold.The LMP statistic and its approximated theoretical detection performance were derived .Simulation results show that the pro-posed method can be used to verify the reliability for blind frequency estimation of sinusoid at low signal-to-noise ratio.